The Dilemma of Knowledge in The Black Heralds (1919). A Rereading of the Poem «The Spider» - Velásquez Ccosi, Luis (2019)
This article proposes that the poems of The Black Heralds and, specially, the referenced poem deconstructs the classic system of a modern science when mobilizes the elements that are put into play, the subject and the object, undoing all hierarchy between them. The poem «The Spider», particularly, is a deep reflection about the knowledge and the possibilities of the knowledge of the subject and inside him, where is fundamental the enunciative position that puts in evidence the concrete particularity in the construction of knowledge, in opposition to the supposed universality of a transcendental subject (Castro-Gómez). In this way, a phenomenological approach of the body of the supposed «object», but also of the «subject», would show the investments that are made in the poem, on the form of an approach to the knowledge of a radical otherness «a spider» (Derrida).